Intranasal Application of Foxp3 Introduced with Poly(d,l-lactic-co-glycolic acid) (PLGA) Nanoparticles (Foxp3 NPs) Attenuates Allergic Inflammation in a Mouse Model of Allergic Rhinitis - Seung Cheol Han; Sunhee Yeon; Hyejeen Kim; Sookyoung Park (Pharmaceutics)
Background: Allergic rhinitis (AR) is a common disease that requires more convenient, safe, and effective therapy. This study aimed to investigate the therapeutic effect of Forkhead box protein3 (Foxp3) introduced with poly(d,l-lactic-co-glycolic acid) (PLGA) nanoparticles (Foxp3 NPs) in an AR mouse model. Methods: A murine model of allergic rhinitis was established using BALB/c mice through initial sensitization by intraperitoneal administration of ovalbumin (OVA), followed by repeated intranasal OVA challenges. Foxp3 plasmid-loaded PLGA nanoparticles were subsequently administered via either the intranasal or intraperitoneal route to evaluate therapeutic efficacy. Episodes of sneezing and nose rubbing were counted. The serum total IgE, OVA-specific IgE, and cytokine levels in nasal lavage fluid (NALF) were determined by ELISA (Enzyme-Linked ImmunoSorbent Assay). Nasal mucosa from each group were analyzed using protein, reverse transcriptase–polymerase chain reaction (RT-PCR), and histological analyses. Result: Rubbing and sneezing symptoms improved in the Foxp3 NPs intranasal administration group. Foxp3 NPs intranasal administration markedly ameliorated OVA-induced nasal allergic inflammation. The total IgE and OVA-specific IgE serum level and IL-4, IL-13 expression levels of NALF were significantly decreased in the treated Foxp3 NPs group. The histopathological results of nasal mucosa were also normal, with no cellular infiltration and no inflammation in the Foxp3 NPs group. Conclusions: These results suggest that Foxp3 NPs alleviate nasal allergic inflammation and may have therapeutic value in the treatment of AR.